Molecular Identification of Lepidopteran Predators of Coccidae on Coffee Plants (Coffea canephora) in Sigi Regency - I Made Budiarsa; Manap Trianto; Bahana Aditya Adnan (Biology, Medicine, & Natural Product Chemistry, 2025)
This study aimed to identify the species of Lepidopteran predators that prey on soft scale insects (Coccidae) found on coffee plants in Sigi Regency using molecular techniques. DNA was extracted using the modified CTAB method (Doyle & Doyle, 1990). PCR amplification targeted the COI gene using universal primers LCO1490 and HCO2198 with a GeneAmp PCR System 9700. Visualization was done using 1% agarose gel and UV-transilluminator. Sequencing was conducted externally. Data were analyzed using BioEdit 7.2.5, BLAST, BOLD Systems, and MEGA11 software. The DNA sequence of the predator sample showed 97.91% similarity to Autoba rubra based on GenBank and 97.59% in BOLD Systems. Phylogenetic analysis confirmed a close genetic relationship with A. rubra, distinct from Eublemma. Morphological similarities with Eublemma were misleading, highlighting the accuracy of molecular identification. This study is the first to confirm the identity of a Lepidopteran predator of coffee scale insects in Indonesia using molecular techniques, revealing its close relation to Autoba rubra. The results correct previous morphological misidentifications and contribute new data on predator diversity in biological control contexts.